2020
DOI: 10.21608/pssjn.2020.29344.1022
|View full text |Cite
|
Sign up to set email alerts
|

Nurses knowledge and practice regarding adverse events of vaccines in expanded program on immunization in health care centers

Abstract: background: As with any drug or medication, vaccines also require special attention because, though they are considered safe and beneficial to control diseases, they can trigger mild or even severe adverse events. Aim: assess nurse's knowledge and practice regarding adverse events of vaccines in expanded program on immunization in health care centers. Research design: A descriptive research design used in the current study. Setting: all available health care centers ( 14) & the only health office in Port Said … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(6 reference statements)
2
1
0
Order By: Relevance
“…Our findings shown that nurses have highest knowledge score in general information about vaccination domain as well as the way to reduce the appearance of adverse events of vaccination. Several studies were supported our findings [1,3,4].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings shown that nurses have highest knowledge score in general information about vaccination domain as well as the way to reduce the appearance of adverse events of vaccination. Several studies were supported our findings [1,3,4].…”
Section: Resultssupporting
confidence: 90%
“…In this study, the level of knowledge among nurses was (62.5%), Our finding is in harmony with the previous study that conducted in Egypt, which shown more than two-thirds of nurses have good knowledge toward vaccination [1]. The overall of good knowledge among nurses could be of some factors as follow:…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation